Global social identity predicts cooperation at local, national, and global levels: Results from international experiments - Grimalda, Gianluca; Buchan, Nancy R.; Brewer, Marilynn B. (Frontiers in Psychology, 2023)
Individuals who identify themselves with humanity as a whole tend to be more prosocial in a number of different domains, from giving to international charities, to volunteering for humanitarian causes. In this paper we show that global identity is “inclusive” in character. That is, rather than neglecting or diminishing the attachment to local and national groups, identification with all of humanity encourages individuals to embrace local and national goals at no lesser intensity than they embrace global goals. We do so using experimental data on social dilemmas at the local level and nested social dilemmas at the local and national level, and at the local and world levels. Experiments were conducted with adult samples in the US, Italy, Russian Federation, Argentina, South Africa, and Iran. We show that the higher the identification with global collectives, net of identification with local and national collectives, the higher cooperation at the local, national, and world levels. Conversely, local social identity is not significantly associated with cooperation at any level of interaction, while national social identity, net of local and global identification, tends overall to have a negative correlation with cooperation, particularly at the local level. We also show that individuals with strong global identity are significantly more optimistic of others’ contribution than individuals with lower levels of global identification, but are as accurate as others in predicting others’ cooperation at the local and national level. Their forecast error is instead systematically larger than all others for cooperation at the world level.